THE IMPACT OF WI-FI ELECTROMAGNETIC RADIATION ON THE ENVIRONMENT (KIUT Publication, 2025)
Wi-Fi is a “wireless communication technology used for local area networks.” Operating at frequencies of 2.4 and 5 GHz, Wi-Fi has become ubiquitous in our modern world. Due to this widespread use, concerns about the safety of Wi-Fi routers have emerged. The aim of this research is to answer the following questions: To what extent and how does Wi-Fi radiation affect the environment? This study employs methods such as online surveys and reviews of current scientific literature. The research contributes to the field of biophysics; however, Wi-Fi routers have a negative impact on the environment.